The Big Data Agenda: Data Ethics and Critical Data Studies - Richterich, Annika (2018)
While working on this book, I have immensely benefitted from the fantastic support of many peers, colleagues and friends. I am very grateful for their advice and encouragement. I would also like to thank those who have contributed to big data discourses, ethics and critical data studies: their insights and their initiation of much-needed debates were invaluable for my work. I am very grateful to my colleagues at Maastricht University’s Faculty of Arts & Social Science. Although more colleagues deserve gratitude, I would particularly like to thank Sally Wyatt, Anna Harris, Vivian van Saaze, Tamar Sharon, Tsjalling Swierstra and Karin Wenz. Their work, advice and support were crucial for this project. My sincere thanks go to Sally Wyatt for her advice and for endorsing my application for a Brocher fellowship. This 1-month visiting fellowship at the Brocher Foundation (www.brocher.ch) allowed me to focus on my book and I would like to thank the foundation as well as its staff. In addition, I tremendously appreciated and enjoyed the company of and the discussions with the other fellows; among them were Laura Bothwell, Alain Giami, Adam Henschke, Katherine Weatherford Darling, Bertrand Taithe, Peter West-Oram and Sabine Wildevuur. I received detailed, much-appreciated feedback and suggestions from the anonymous reviewers. I would like to thank them for their time and their elaborate comments which were incredibly helpful for revising the manuscript. Moreover, I am very grateful to Andrew Lockett, from University of Westminster Press, and Christian Fuchs, editor of the Critical, Digital and Social Media Studies series, for supporting this book and for enabling its open access publication. Last, though certainly not least, I would like to thank my family, my parents and my brothers, for being as supportive and understanding as ever. I would like to thank my partner, Stefan Meuleman, not only for patiently allowing me the time and space needed to complete this project, but also for his advice on the book and for making sure that I take time away from it too.